ROAD-MAP FOR CONDUCTING MEDICAL EXAMS IN RESOURCE LIMITED COUNTRIES DURING COVID-19 PANDEMIC - Muhammad Shabbir; Farooq Abdullah; Muath Al Ammar; Niaz Ali (Khyber Medical University Journal, 2022)
The COVID-19 pandemic has adversely affected medical education worldwide. Developed countries have successfully managed this by adopting modified ways of teaching and assessment and utilizing their resources but low income countries have struggled in managing the challenges they have faced in teaching and assessment. Medical exams have been postponed multiple times because of no clear way forward due to limited resources. This has not only resulted in wasting of the time of students but also adds to desperation and frustration of the students as well as teachers and institutes. Newer modes of information transfer including E-lectures, pre-recorded videos, simulation based learning and assessment (Kahoot, Socrative etc) have been introduced over the past two years. This paper illustrates a modified model for medical exams which may prove a suitable alternative for low income countries during pandemic.